The Characteristics of the HIV-1 Env Glycoprotein Are Linked With Viral Pathogenesis - Pérez-Yanes, Silvia; Pernas, María; Marfil, Silvia; Cabrera-Rodríguez, Romina; Ortiz, Raquel; Urrea, Víctor; Rovirosa, Carla; Estévez-Herrera, Judith; Olivares, Isabel; Casado, Concepción; Lopez-Galindez, Cecilio; Blanco, Julià; et al. (Frontiers in Microbiology, 2022)
The understanding of HIV-1 pathogenesis and clinical progression is incomplete due to the variable contribution of host, immune and viral factors. The involvement of viral factors has been investigated in extreme clinical phenotypes from rapid progressors to long-term non-progressors (LTNPs). Among HIV-1 proteins, the envelope glycoprotein complex (Env) has concentrated many studies for its important role in the immune response and in the first steps of viral replication. In this study, we analyzed the contribution of 41 Envs from 24 patients with different clinical progression rates and viral loads (VLs), LTNP-Elite Controllers (LTNP-ECs); Viremic LTNPs (vLTNPs), and non-controller individuals contemporary to LTNPs or recent, named Old and Modern progressors. We studied the Env expression, the fusion and cell-to-cell transfer capacities as well as viral infectivity. The sequence and phylogenetic analysis of Envs were also performed. In every functional characteristic, the Envs from subjects with viral control (LTNP-ECs and vLTNPs) showed significant lower performance compared to those from the progressor individuals (Old and Modern). Regarding sequence analysis, the variable loops of the gp120 subunit of the Env (i.e., V2, V4 and mainly V5) of the progressor individuals showed longer and more glycosylated sequences than controller subjects. Therefore, HIV-1 Envs from virus of patients presenting viremic control and the non-progressor clinical phenotype showed poor viral functions and shorter sequences, whereas functional Envs were associated with virus of patients lacking virological control and with progressor clinical phenotypes. These correlations support the role of Env genotypic and phenotypic characteristics in the in vivo HIV-1 infection and pathogenesis.